The predictive factors affecting false positive in on-site operated CT-fractional flow reserve based on fluid and structural interaction - Kawaguchi, Yuko O.; Fujimoto, Shinichiro; Kumamaru, Kanako K.; Kato, Etsuro; Dohi, Tomotaka; Takamura, Kazuhisa; Aoshima, Chihiro; Kamo, Yuki; Kato, Yoshiteru; Hiki, Makoto; Okai, Iwao; Okazaki, Shinya; et al. (International journal of cardiology. Heart & vasculature, 2019)
A novel algorithm has been developed for the on-site analysis of CT-fractional flow reserve (CT-FFR) using fluid structural interactions. There have been no reports on the factors affecting the diagnostic performance of CT-FFR using this algorithm. We evaluated the factors predictive of false-positive CT-FFR findings compared to invasive FFR as a reference standard. The subjects were 66 consecutive cases (81 vessels) who underwent invasive FFR assessment within 90 days of the detection of 30–90% stenosis of one vessel of the major coronary artery, from among patients with suspected coronary arterial disease who underwent one-rotation scanning by 320-row coronary CT angiography (CCTA). The prospective CCTA mode was used for all patients, with the X-ray exposure set in a range of 70–99% of the RR interval. The FFR was calculated on-site from multiple cardiac phases. Factors associated with a false-positive finding of functional stenosis on CT-FFR, defined as an invasive FFR of ≤0.80, were evaluated using logistic regression analysis. Thirty-nine vessels (48.1%) had an invasive FFR of ≤0.80. CT-FFR and invasive FFR values disagreed in 13 vessels in 13 patients. The values were false positive in 12 of the vessels. In an analysis of patient characteristics, the body mass index (odds ratio, 1.33; 95%CI, 1.06–1.67; p = 0.01) and Image noise (odds ratio, 1.18; 95%CI, 1.01–1.40; p = 0.04) were predictive of false-positive findings. The presence of calcified plaque (odds ratio, 5.16; 95%CI, 1.06–20.85; p = 0.01) was the only significant predictive factor in a vessel-based analysis of lesion characteristics. The presence of calcified plaque exerted a significant effect on the diagnostic performance of CT-FFR, and did so independently of the degree of calcification indicated by the Agatston score.